IS INFLAMMATION AN AGE-RELATED CAUSE OF BPH PROGRESSION - Herman, Hendra; Hamid, Agus Rizal AH; Mochtar, Chaidir Arif (Indonesian Journal of Urology, 2011)
Objective: To find the role of inflammation in BPH progression represented by prostate enlargement compared between age group. Material & method: Tissue samples of BPH were collected from biopsy, transurethral resection or open surgery. Clinical information was collected including such as patient age, prostate volume, serum prostate specific antigen (PSA) and history of retention before procedure. Patients were divided into three groups, below 63 years old (young adult), 63 - 69 years old (older adult) and equal or above 70 years old (elderly). The samples were analyzed to define the microscopic structure of the hyperplasia (stromal or glandular) and to detect prostatic intraepithelial neoplasia, atypical stromal acinic proliferation, atypical acinar hyperplasia or prostate cancer. Prostate cancer was excluded from study samples. Grade of inflammation was determined by a pathologist depending on number of inflammatory cells. Grade of inflammation was classified in two groups, with mild inflammation or moderate-to-severe inflammation. Results: A total of 1189 patients were reviewed, 1172 were diagnosed with BPH. There were 381 patients (32,5%) with age below 63 years old (young adult), 380 (32,4%) between 63-69 years old (older adult) and 411 (35,1%) in equal or above 70 years old (elderly). In young-adult group, median of prostate volume between mild and moderate to severe inflammations was 42,56 and 45,75 (p = 0,500), for older adult group median was 45,00 and 51,00 (p = 0,038), for elderly group median was 49,00 and 51,98 (p = 0,621). Conclusion: Inflammation has a role in progression of prostate enlargement especially for the older adult group. Keywords: inflammation in BPH progression, prostate volume, age, PSA.